Engaged Pedagogy Dialogue and Critical Reflection - Boys, Mary C. (Teaching theology and religion, 1999)
This article challenges faculty to adopt “engaged pedagogies” that are grounded in dialogue and critical reflection. It first situates this challenge in the academic culture where the scholarship of teaching is given little attention. Then it highlights the importance of conversation, a fundamental aspect of dialogue, and develops the radical character of dialogical teaching. The article then turns to ways in which critical reflection might foster dialogue.